2015
DOI: 10.1038/ncomms7841
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Bak α1 helix from the core and latch domains is required for apoptosis

Abstract: During apoptosis, Bak permeabilizes mitochondria after undergoing major conformational changes, including poorly defined N-terminal changes. Here, we characterize those changes using 11 antibodies that were epitope mapped using peptide arrays and mutagenesis. After Bak activation by Bid, epitopes throughout the a1 helix are exposed indicating complete dissociation of a1 from a2 in the core and from a6-a8 in the latch. Moreover, disulfide tethering of a1 to a2 or a6 blocks cytochrome c release, suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 41 publications
8
73
1
Order By: Relevance
“…1F). We have previously shown that tethering V142C (α5) to F150C (α6) to constrain "core/latch" dissociation still shows evidence of cBID-induced N-terminal epitope exposure, indicating that cBID still interacts with the tethered form to induce early steps in BAK conformation change (19). However, in contrast with the α1:α2 and α1/2 loop:α6 tethers, tethering α5:6 failed to stabilize the cBID:BAK complex (Fig.…”
Section: Bak Conformation Change Destabilizes the Cbid:bak Interactiomentioning
confidence: 81%
See 2 more Smart Citations
“…1F). We have previously shown that tethering V142C (α5) to F150C (α6) to constrain "core/latch" dissociation still shows evidence of cBID-induced N-terminal epitope exposure, indicating that cBID still interacts with the tethered form to induce early steps in BAK conformation change (19). However, in contrast with the α1:α2 and α1/2 loop:α6 tethers, tethering α5:6 failed to stabilize the cBID:BAK complex (Fig.…”
Section: Bak Conformation Change Destabilizes the Cbid:bak Interactiomentioning
confidence: 81%
“…To define the step in BAK activation at which cBID dissociates we used additional constraints between the α1-α2, α1-α6, and α5-α6 that we have shown impair defined steps in BAK activation to block cytochrome c release (7,19) (Fig. 1E).…”
Section: Bak Conformation Change Destabilizes the Cbid:bak Interactiomentioning
confidence: 99%
See 1 more Smart Citation
“…These changes suggest that the α1-α2 loop separates from α1, consistent with increased labelling of A54C in the α1-α2 loop that opposes α1. Thus, increased labelling of cysteine residues placed throughout the N-segment, α1 and the α1-α2 loop, together with exposure of several N-terminal antibody epitopes (Alsop et al, 2015), indicate that the Bak N-terminus becomes completely solvent-exposed after activation ( Figure 1D).…”
Section: The Bakmentioning
confidence: 99%
“…In contrast, nonactivated Bax is largely cytosolic due to binding of α9 to its own hydrophobic groove (Wolter et al, 1997, Gahl et al, 2014. Following binding of BH3-only proteins, both Bak and Bax undergo similar conformation changes including α1 dissociation (Weber et al, 2013, Alsop et al, 2015 and separation of the "latch" domain (α6-α8) from the "core" domain (α2-α5) (Czabotar et al, 2013, Brouwer et al, 2014. The core and α6 then collapse onto the membrane surface and become shallowly inserted into the membrane to lie in-plane (Aluvila, 2014, Bleicken et al, 2014.…”
Section: Introductionmentioning
confidence: 99%